Computer-assisted needle navigation for pediatric internal jugular central venous cannulation: A feasibility study. Issue 6 (November 2020) - Gallo, Christopher; Foroughi, Pezhman; Meagher, Elisabeth; Vellody, Ranjith; Yadav, Bhupender; Ho, Anthony; Demir, Alican; Heisenberg, Dorothee; Cleary, Kevin; Sharma, Karun
Introduction: Vascular access for central venous catheter placement is technically challenging in children. Ultrasound guidance is recommended for pediatric central venous catheter placement, yet many practitioners rely on imprecise anatomic landmark techniques risking procedure failure due to difficulty mastering ultrasound guidance. A novel navigation system provides a visual overlay on real-time ultrasound images to depict needle trajectory and tip location during cannulation. We report the first pediatric study assessing feasibility and preliminary safety of using a computer-assisted needle navigation system to aid in central venous access. Methods: A prospective, institutional review board–approved feasibility study was performed. All participants provided written informed consent. Ten patients (mean age: 11.4 years, five males) underwent central venous catheter placement with ultrasound and navigation system guidance. All procedures were performed by interventional radiologists expert in vascular access. Feasibility was measured through binary (yes/no) responses from participating users assessing device usability and feasibility. The number of needle passes and procedure time measures were also recorded. Results: Internal jugular veins (seven right sided, three left sided) were cannulated in all patients with no complications. Users confirmed navigation system feasibility in all 10 participants. Mean vein diameter and depth was 13.3 × 9.8 ± 3.4 × 2.1 and 7.0 ± 1.7 mm, respectively. Successful cannulation occurred in all patients and required only a single needle pass in 9 of 10 patients. Mean device set-up and vascular access times were 5:31 ± 2:28 and 1:48 ± 2:35 min, respectively. Conclusion: This pilot study suggests that it is feasible to use a novel computer-assisted needle navigation system to safely obtain central venous access under ultrasound guidance in pediatric patients.